The mediating role of trust in the adoption of e-goverment services by community in the university of tripoli - Ali Salem, Amer Salem (2017)
Governments are striving to serve citizens in better way. The introduction of electronic government (e-Government) has provided citizens with several advantages. However, citizens are not using the e-Government services. Studies in this field are dominated by developed countries. Few studies conducted in developing countries. The purpose of this study is to investigate the factors that influence the adoption of e-Government services in Libya. Building on the literature, the study has deployed the unified theory of acceptance and use of technology (UTAUT) along with security and trust. Three main constructs were incorporated including individual factors with sub-constructs including performance expectancy, effort expectancy, social influence, and IT knowledge. The second construct is technological factors and it includes facilitating condition, security, and privacy. Third construct is trust and it includes trust in government and trust in Internet. Trust is proposed as a mediator. The study is quantitative in nature. A questionnaire is used as an instrument of data collection. Using stratified sampling technique, the data was collected from 441 students, academic staff, and non-academic staff at University of Tripoli. The findings showed that individual factors and technological factors have significant influence on behavioral intention to adopt e-Government services. Factors that influence the adoption of e-Government services in Libya are performance expectancy, social influence, IT knowledge, trust in Internet, facilitating condition, privacy, and security. Trust plays a partial mediating role between technological factors and behavioral intention. Increasing the participation in e-Government services will have significant effect on public expenditure and the citizens’ satisfaction. In addition, decision makers can utilize the findings of this study to increase the acceptance and use of e-Government services in Libya. More qualitative studies with different variables and respondents are needed to establish the factors that affect the acceptance and use of e-Government services in Libya.